EKSISTENSI AKUNTAN DALAM PERUSAHAAN HINGGA KONTRIBUSI KE EKONOMI di ERA REVOLUSI INDUSTRI 4.0 DAN SOCIETY 5.0 - Rustandi, Tata; Husni, Mohamad (Yayasan Education and Social Center, 2024)
The purpose of this study is to look at the direction and strategic position of an accountant and the contribution of an accountant to the economy during the industrial revolution 4.0 and society 5.0, these changes can be a threat or opportunity for the position of an accountant in a corporation, many studies state that 47% of jobs are directly will be automated, including accountants, all of this is from the development of a technology that directly underlies the industrial revolution 4.0 and society 5.0. in the East Serang industrial area, furthermore the results of this study confirm that an accountant will get a strategic position in the corporation and the economy in the era of industrial revolution 4.0 and society 5.0 by: 1. digitizing capabilities in scientific development his. 2. Implement new technology on an ongoing basis. 3. The competency base has begun to shift from a national basis to an international basis. 4. Respond to changes in technology, both industrial technology and business technology. 5. Human-digital skills have become a learning curriculum for all educational institutions